Recommended Medical Record Practices for Student-Run Free Clinics - David Smeenge; Bradley Larson; Margit Chadwell; Juliann Binienda (Journal of Student-Run Clinics, 2016)
Although well-intentionedÂÂ, free clinics may overlook details pertaining to the protection of patient information and maintenance of medical records. Providing students may not know about important regulations and practices which are currently in place to protect patients. For example, it is necessary for a business associate agreement to be signed with respective data managing providers prior to using an online cloud storage provider. This article is a summary of reasonable and prudent tips for free clinics to follow and includes: the proper handling of patient information, what to include in patient notes, who may write notes, and ensuring that notes are signed in a timely manner.